Inhibition of the mutagenic effects of N-methyl-N′-nitro-N-nitrosoguanidine and 9-Aminoacridine by indenopyridines in the Salmonella typhimurium tester strain 1537 and E. coli - Turhan, Kadir; Ozturkcan, S. Arda; Turgut, Zuhal; Karadayi, Mehmet; Gulluce, Medine (INFORMA HEALTHCARE, 2014)
The goal of the present research was to determine the protective potential of five newly synthesized indenopyridine derivatives against N-methyl-N'-nitro-N-nitrosoguanidine (MNNG) and 9-aminoacridine (9-AA) induced mutagenesis. MNNG sensitive Escherichia coli WP2uvrA and 9-AA sensitive Salmonella typhimurium TA1537 were chosen as the bacterial tester strains. All of the test compounds showed significant antimutagenic activity at various tested concentrations. The inhibition rates ranged from 25.6% (Compound 2 - 1 mM/plate) to 68.2% (Compound 1 - 2.5 mM/plate) for MNNG and from 25.7% (Compound 4 - 1 mM/plate) to 76.1% (Compound 3 - 2.5 mM/plate) for 9-AA genotoxicity. Moreover, the mutagenicity of the test compounds was investigated by using the same strains. None of the test compounds has mutagenic properties on the bacterial strains at the highest concentration of 2.5 mM. Thus, the findings of the present study give valuable clues to develop new strategies for chemical prevention from MNNG and 9-AA genotoxicity by using synthetic indenopyridine derivatives.
Keywords: Ames/Salmonella test; antimutagenicity; E. coli WP2 test; indenopyridine derivatives; indenopyridines; mutagenicity; REVERSE MUTATION ASSAY; ANTIMUTAGENIC ACTIVITY; HANTZSCH REACTION; ESCHERICHIA-COLI; DERIVATIVES; 1,4-DIHYDROPYRIDINES; RESPONSES; CDB-4022; EXTRACT; RAT; Chemistry; Pharmacology & Pharmacy; Toxicology